Residential willingness to pay for deep decarbonization of electricity supply: Contingent valuation evidence from Hong Kong. (October 2017) - Cheng, Y.S.; Cao, K.H.; Woo, C.K.; Yatchew, A.
Abstract: Motivated by the government's proposed target of reducing CO2 emissions by 30% of the 2005 level in the year 2020, we estimate the residential willingness-to-pay (WTP) for deep decarbonization of Hong Kong's electricity supply, which is heavily dependent on coal-fired generation. Our contingent valuation survey conducted in 2016 of 1460 households yields dichotomous choice data based on the respondents' answers to a series of closed-ended questions. Such data are less susceptible to the strategic bias that often plagues self-stated WTP data obtained by direct elicitation via open-ended questions. Using binary choice models, we find that average WTP is 48–51%, relative to current bills, if the decarbonization target is achieved via natural gas generation and renewable energy. However, estimated WTP declines to 32–42% when decarbonization entails additional nuclear imports from China. As the projected bill increase caused by the target's implementation is 40%, our WTP estimates support the government's fuel mix policy of using natural gas and renewable energy to displace Hong Kong's coal generation. Highlights: Collect dichotomous choice data on Hong Kong's deep decarbonization policy. Use the choice data to estimate residential willingness-to-pay (WTP). Report WTP estimates for Hong Kong's decarbonization target of 30% by 2020. Conclude that Hong Kong households support deep decarbonization.